Menelisik Perubahan Pandangan Tentang Konsep Nikah di Era Digital - Ahmad Habib Dairobi; Nurasiah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The rapid development of digital technology has significantly transformed how Muslim communities understand and practice the concept of marriage. This study aims to examine how the digital era reshapes societal perceptions of marriage within the framework of Islamic Family Law, identify digital factors that influence contemporary understandings and practices of marriage, and analyze Islamic legal responses to these emerging phenomena. The research employs a literature-based method by analyzing classical fiqh sources, Indonesian positive legal regulations, and contemporary studies on digital culture and modern marital practices. The findings reveal that the digital era has reconstructed social perceptions of relationships, partner selection processes, and marital preparation through social media, matchmaking applications, and increasingly accessible information flows. Furthermore, phenomena such as online marriages, long-distance marriage contracts, and the digitalization of marital administration have become part of current Islamic family law dynamics. Islamic Family Law responds to these changes through adaptive approaches, including contemporary ijtihad and regulatory adjustments that uphold core principles of the Sharia. This study emphasizes the importance of contextualizing the concept of marriage in the digital age to ensure that Islamic values remain relevant amid ongoing technological advancements.